Haemolysis, Biofilm and Virulence Determinants of Escherichia coli Isolated from Bovine Calf Diarrhea - Sikrodia, Ravi; Chhabra, Daljeet; Audarya, S. D.; Jogi, Joycee; Gangil, Rakhi; Sharda, Rakesh; Jatav, G. P. (International Journal of Bio-resource and Stress Management, 2025)
The research was conducted during July, 2021 to April, 2022 in the Department of Veterinary Microbiology, College of Veterinary Science and Animal Husbandry, Mhow (M.P.), India, with the objective of isolating and characterizing Escherichia coli strains from diarrheic calves using both phenotypic and molecular techniques. A total of 250 diarrheic fecal samples were obtained from calves exhibiting clinical symptoms such as dehydration, watery feces, and poor appetite. These samples were then immediately transported to the laboratory under aseptic and cold conditions for the isolation and further identification of E. coli. Nutrient agar, EMB agar and Blood agar were used for the isolation and characterization. From the processed samples, 124 E. coli isolates were obtained, indicating an overall incidence rate of 49.6%. Out of the 124 isolates, 15 (12.09%) showed haemolysis on blood agar, whereas 109 (87.9%) were non-hemolytic. Biofilm formation was demonstrated in 60 isolates (48.38%) by the tube method and in 63 isolates (50.80%) using the Modified Congo Red Agar method. Among the 124 isolates, 90 (72.58%) tested positive for invasiveness through Congo red dye binding assay (CR+). In serotyping, multiple O-types including O126, O17, O2, O7, O111, O101, O57, O135, O120, O63, O88, O121, O26, O11, O157, and O18 were identified, while six isolates were untypable for the “O” antigen. Singleplex PCR detected the fimH gene in 70% and the ompT gene in 100% of the isolates.